Adhesive Bonding of Resin Composite to Various Ni-Cr Alloy Surfaces Using Different Metal Conditioners and a Surface Modification System - Almilhatti, Hercules Jorge; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Goncalves Betiol, Ederson Aureo (Wiley-Blackwell, 2009)
Purpose: This study evaluated the effect of three metal conditioners [Metal Photo Primer (R) (MPP), Cesead II Opaque Primer (R) (OP), Targis Link (R) (TL)], and one surface modification system [Siloc (R) (S)] on the shear bond strength (SBS) of a prosthetic composite material to Ni-Cr alloy.Materials and Methods: Rivet-shaped specimens were cast, and three surface treatments were evaluated: Polishing (P); sandblasting with either 50 mu m (50SB) or 250 mu m (250SB) Al(2)O(3). All products were applied to half of the specimens, while the other half remained without the materials. Veneering resin composite (8-mm diameter, 2-mm thick) was applied and light-exposed for 90 seconds in a laboratory light-curing unit. The specimens were stored in water at 37 degrees C for 24 hours, and half were subjected to 500 thermal cycles consisting of water baths at 4 degrees C and 60 degrees C. All specimens were submitted to SBS test (0.5 mm/min) until failure. Failure patterns were determined using optical and scanning electron microscope (SEM) analysis. Data were analyzed by ANOVA and post hoc Tukey's test (preset alpha of 5%).Results: The SBS values of OP and TL groups were higher than those of MPP and S within the 50SB treatment (p < 0.05). No significant difference in SBS was noted between OP and TL as well as between MPP and S. on the other hand, no significant differences were found among conditioners within the 250SB group (p > 0.05). The SBS values of MPP, OP, and S from the 250SB group were higher than those from 50SB (p < 0.05). No significant difference in SBS was noted among most groups with conditioners after thermocycling. The only exception was observed for MPP, which showed an increase in SBS after thermocycling (p < 0.05). Differences in SBS were noted among the groups with conditioners (p < 0.05), and no significant difference in SBS was noted between TL and OP groups, which showed the highest values among all within the P group. No significant difference was noted between MPP and S. Debonded surfaces showed adhesive failures predominantly located between metal surface and opaque resin.Conclusions: The OP and TL conditioners and surface sandblasting with 250 mu m Al(2)O(3) promoted the highest SBS between resin and the Ni-Cr metal surface.
Keywords: Alloys; shear bond strength; fixed prosthodontics; metal conditioners; surface modification; composite resin